NEW MULTIAXIAL CYCLE COUNTING METHOD BASED ON CRITICAL PLANE - YUAN LiangXin (Jixie qiangdu)
In critical plane method,a proper cycle counting method should be selected when processing shear components history which perpendicular to each other and parallel to the critical plane such as Case B crack. The MWB method is discussed and optimized firstly and a new multiaxial loading counting method based on critical plane was developed. The new method regarded shear strain as main channel and normal strain as auxiliary channel. According to memory rule for material deformation,counting interval was divided into sub-interval and independent interval step by step. Finally,the new method,Wang-Brown method and MWB method was applied to count a non-proportion multiaxial loading and predict rake dozer H-frame fatigue life respectively,the results show the new method can extract damage event and predict fatigue life accurately.